Comparative Study of Molar Refraction and Polarizability Constants of Novel 1-Furyl-3-(substituted phenyl)-2-propene-1-one in Different Percentages of Solvents - H. Bhendkar, Amol; P. Deohate, Pradip; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2016)
The refractive indices and densities of 1-furyl-3-(substituted phenyl)-2-propene-1-one (I-VI) in different percentages of dioxane-water, ethanol-water and acetone-water mixtures have been measured. The data have been used to calculate the molar refraction and polarizability constants for the compounds which have been used to detect the nature of dipoles and to compare the 1-furyl-3-(substituted phenyl)-2-propene-1-one (I-VI) on the basis of presence of different substituents.